Pengaruh Kepemimpinan, Lingkungan Kerja, dan Kemampuan Kerja Terhadap Kinerja Karyawan - Ella Anastasya Sinambela; Utami Puji Lestari (STKIP PGRI SITUBONDO, 2022)
Human resources are one of the factors to achieve company goals. Increased human resources can be capital to face market competition. One of them is by increasing employee performance. Increased employee performance is influenced by a few factors, including leadership, work environment, and work ability. This study aims to determine the effect of leadership, work environment and work ability on employee performance. The population of this associative research is all employees who work in a company engaged in the manufacture of handicrafts in the city of Malang. The sampling technique of this research is the census. There are 92 respondents in this study. In this study, the analytical technique used is multiple linear regression. The findings of this study are leadership has a significant influence on employee performance. The work environment variable also has a significant influence on employee performance. In addition, work ability also has a significant influence on employee performance. The three independent variables studied in this study have a significant effect on employee performance simultaneously.